Plan de negocios: proyecto inmobiliario conjunto habitacional Portal de Lago - Flores Navarrete, Pablo Javier (2020)
Due to the delicate economic situation the country is going through, it is necessary to search for new sources of income that can diversify the business and have another job besides the public sector that is clearly hit, with greater competition and less profitability. Therefore, through the construction of real estate complexes, they have sought to have their own work and cover the high demand for quality own housing that exists in Lago Agrio. This study has been developed in search of modern, functional designs that adapt to the conditions that exist in Lago Agrio but that provide better benefits than those currently affected are not of good quality, the vast majority, because they have been built without technical advice through artisanal construction. The aim is to provide the population with access to good quality homeowners with affordable prices, focusing on an important market niche with purchasing power to finance the purchase of homes with credits in the public and private financial sector, selling power without problems, thus obtaining minus the minimum profit expected by investors. This sector has been defined through a market study, which has allowed establishing at the socio-economic level, developing the various strategies, components, location of the project that meets the needs of customers.